2015
DOI: 10.1016/j.bpj.2015.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Isocost Lines Describe the Cellular Economy of Genetic Circuits

Abstract: Genetic circuits in living cells share transcriptional and translational resources that are available in limited amounts. This leads to unexpected couplings among seemingly unconnected modules, which result in poorly predictable circuit behavior. In this study, we determine these interdependencies between products of different genes by characterizing the economy of how transcriptional and translational resources are allocated to the production of proteins in genetic circuits. We discover that, when expressed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
362
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(380 citation statements)
references
References 43 publications
(44 reference statements)
18
362
0
Order By: Relevance
“…GFP transcription was constitutively driven from the P tet promoter and the host or oribosome pool utilised for translation, controlled by selection of RBS as described above. We determined the level of coupling between the two circuit genes by observing the slope of the isocost line of circuit gene expression during exponential growth; this quantifies the change in GFP as RFP is induced 3 (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…GFP transcription was constitutively driven from the P tet promoter and the host or oribosome pool utilised for translation, controlled by selection of RBS as described above. We determined the level of coupling between the two circuit genes by observing the slope of the isocost line of circuit gene expression during exponential growth; this quantifies the change in GFP as RFP is induced 3 (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, many initial designs fail upon implementation in vivo due to unforeseen interactions between the host and synthetic circuit 2 . These often arise due to competition for shared cellular resources, such as RNA polymerases and ribosomes 3,4 . Previous experimental studies have shown that translational capacity, in the form of free ribosomes, limits microbial gene expression 3,[5][6][7][8] and so is a key cause of these hidden interactions 4 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these couplings originate from the usage of shared resources of the transcriptional and translational machinery. The influence of such limited pools of resources has been addressed just recently by Gyorgy et al (2015); Weiße et al (2015); Gorochowski et al (2016), where both experimental and computational approaches are being discussed. For the purpose of describing interactions of several genes and their products, the stated works mainly use Hill-kinetics to phenomenologically describe protein production depending on the concentration of certain transcription factors.…”
Section: Introductionmentioning
confidence: 99%